Sosialisasi Perubahan Nomor Pokok Wajib Pajak (NPWP) Orang Pribadi menggunakan Nomor Induk Kependudukan (NIK) Kepada Masyarakat Kelurahan Cawang - Jisman M. Lubis; Beatrix Delfina; Lenny Panggabean; Daniel Owen; Christopher Caesar (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
Enforcement of Minister of Finance Regulation (PMK)-112/PMK.03/2022 regarding NPWP for Individual Taxpayers, Corporate Taxpayers, and Government Agency Taxpayers which is the implementation of the mandate of the Law on Harmonization of Tax Regulations which stipulates that Taxpayer Identification Numbers (NPWP) of individuals who are Indonesian residents using a Population Identification Number (NIK). Using the Community Education method which aims to increase understanding and awareness of the Cawang community regarding PMK-112. PkM is carried out by several lecturers from the tax management study program by cooperating with the Cawang District Office as partners of the University and the Office of the Directorate General of Taxes for the East Jakarta Region and also used a questionnaire. The questionnaire was filled out by 60 respondents, the majority of respondents were female and aged 41 to 50 years, with an income below IDR 5,000,000,- with a high school education level and the majority had attended extension services and socialization of taxation. For understanding tax regulations, especially PMK-112, it can be seen that many participants still do not understand tax regulations. There needs to be more intense outreach, both organized by the Directorate General of Taxes and the university.